Pengaruh pemberian insektisida Furadan 3G terhadap perkembangan tuba neuralis embrio ayam ras - Siti Akbari; Leonardo Lubis (Bali Anatomy Journal, 2018)
Background: Furadan 3G insecticide is widely used in agriculture sector. Aim: To explore the teratogenic effect on development of the neural tube and cerebellum of the chick embryo. Method: Eighty fertilized eggs were involved in this experiment and incubated until hatching and forty further (the half) were injected with Furadan 3G 11 mg/kg on the first day of the experiment while the other half were referred as control group. The specimen were studied on the day of 5th, 7th, 21st, 2 weeks and 4 weeks of incubation after hatching by preparing a transversal section and staining with M.E. Conclusion: the Furadan 3G interfered the development of cerebellar cortex.